Return to Physical Activity following Flatfoot Reconstruction. Issue 2 (April 2022) - Fuller, Robert; Eble, Stephanie K.; Day, Jonathan; Rajan, Lavan; Cororaton, Agnes D.; Deland, Jonathan T.; Fuller, Robert; Ellis, Scott J.
Category: Hindfoot; Midfoot/Forefoot; Sports Introduction/Purpose: Progressive collapsing foot deformity (PCFD) is a condition encompassing multiple interrelated, progressive bony and soft tissue deformities, often requiring surgical correction. Patients are often debilitated, with postoperative goals commonly cited as walking and low-impact activities without pain. However, some patients engage in sports and more rigorous activities. Surgeons may struggle to set expectations after surgery since few studies investigate returns to activity following flatfoot reconstruction and every patient is different. Existing studies are limited by small sample sizes, lack of data of activity-specific data, and cohorts confined to one or two of the many possible concomitant procedures in flatfoot reconstruction. This study aims to provide the first generalizable assessment of returns to sports and physical activity following reconstruction surgery in patients with flexible PCFD. Methods: Patients who underwent reconstructive surgery from February 2016-May 2019 for flexible-stage PCFD were identified by registry review and contacted with IRB approval. 70/119 patients (72/121 feet, 60%) were reached at mean 3.1 (range, 2.0 to 5.4) years post-operatively with mean age 43.5 (range, 18 to 59) years at surgery. Concomitant procedures were noted. Physical activity was evaluated with a previously published questionnaire that assessed participation in 15 sports and activities, allowed patients to list additional activities, and classified activities as high or low-impact. Patients specified postoperative number of sessions per week, session duration, return times to participation and maximal activity, relative pre/postoperative difficulty, and satisfaction with outcome regarding sports. Clinical outcomes were evaluated with Patient-Reported Outcomes Measurement Information System (PROMIS) scores. Multivariable regressions assessed associations between PROMIS domain changes and survey responses and linear models measured association of sports participation with the most performed procedures, controlling for concomitant procedures. Results: Patients experienced significant improvements in all PROMIS domains except Depression and surpassed previously reported minimal clinically important differences for PCFD in Physical Function and Pain Interference scores. Patients reported participation in 21 specific sports and activities (Table 1). Compared to preoperatively, patients rated 16.7% (45/270) of activities as more difficult postoperatively, 33.3% (90/270) as equally difficult, and 50% (135/270) as less difficult. Median return times were 6-9 months for participation in activities and 13-18 months to reach maximum preoperative participation. Patients spent a median 7.6 (range, 0-29.8) hours/week engaged in physical activity. 3% of patients (2/72) were sedentary, 31% (22/72) were moderately active, 28% (20/72), were highly active and 36% (26/72) were extremely active. Improvements in Physical Function ( P =.021), Pain Interference ( P =.001), and Global Physical Health ( P =.001) were associated with increased outcome satisfaction regarding physical activities. No associations were found between procedures performed and any PROMIS domains or return parameters. Conclusion: This is the largest and most comprehensive analysis of patient participation in sports and physical activities following flatfoot reconstruction. Results suggest that flatfoot reconstruction surgery generally results in good returns to physical activity in terms of return time, pre-postoperative difficulty changes, and satisfaction. Some patients reported increased difficulty or inability to return to their preoperative maximum level of participation, indicating that flatfoot reconstructions can lead to some athletic limitations. However, ninety percent of patients reported satisfaction with their surgical outcomes with respect to returns to physical activity, indicating that, for most patients, flatfoot reconstruction provides meaningful relief from debilitation.